Cost-effectiveness analysis of combination therapies involving novel agents for first/second-relapse patients with multiple myeloma: a Markov model approach with calibration techniques - Weijia Wu; Fengyuan Tang; Yannan Wang; Wenqianzi Yang; Zixuan Zhao; Yuan Gao; Hengjin Dong (Health Economics Review)
Abstract Background As the number of randomized clinical trials (RCTs) demonstrating the survival benefits of combination therapies in previously treated multiple myeloma (MM) patients increases, it is essential to determine the most cost-effective treatment through robust economic evaluation. This study aims to assess the cost-effectiveness of combination therapies for first/second-relapse MM patients from the perspective of the Chinese healthcare system. Methods A Markov model was developed to evaluate three combination therapy groups based on primary drugs (bortezomib, lenalidomide, and carfilzomib). The economic evaluation was conducted within each group individually, rather than across different groups. Clinical inputs for the model were derived from RCT reports, while healthcare costs were sourced from the Zhejiang Province bidding database and a retrospective analysis. Utility values were obtained through an on-site survey using the Chinese version of the EuroQoL Five-dimensional Five-level Questionnaire. One-way and probabilistic sensitivity analyses were performed to assess the robustness of the base-case results. Results In the bortezomib group, bortezomib-dexamethasone (Vd) yielded 2.42 quality-adjusted life years (QALYs) at a cost of ¥783,775. With a willingness-to-pay (WTP) threshold of three times the 2023 per capita GDP in China (¥258,074), pomalidomide-bortezomib-dexamethasone was the most cost-effective therapy (¥86,129/QALY) in this group. In the lenalidomide group, lenalidomide-dexamethasone (Rd) resulted in 3.06 QALYs at a cost of ¥840,509. Compared to Rd, the incremental cost-effectiveness ratios (ICERs) of elotuzumab-lenalidomide-dexamethasone (¥5,095,300/QALY), ixazomib-lenalidomide-dexamethasone (¥1,605,712/QALY), carfilzomib-lenalidomide-dexamethasone (¥955,255/QALY), and daratumumab-lenalidomide-dexamethasone (¥851,933/QALY) all exceeded the WTP threshold. In the carfilzomib group, carfilzomib-dexamethasone (Kd) resulted in 3.19 QALYs at a cost of ¥1,961,624. Compared to Kd, the ICERs of daratumumab-carfilzomib-dexamethasone (¥2,250,821/QALY) and isatuximab-carfilzomib-dexamethasone (¥4,977,964/QALY) also exceeded the WTP. Sensitivity analyses confirmed the robustness of the base-case results. Conclusions Although this study did not fully account for the heterogeneity of subsequent treatment regimens among first/second-relapse MM patients, it highlights that the substantial financial burden associated with combination therapies involving novel agents poses a significant challenge in justifying their economic value.